2016
DOI: 10.3109/14767058.2016.1143927
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcomes in women with bariatric surgery as compared with morbidly obese women

Abstract: In general, women who undergo bariatric surgery have improved pregnancy outcomes as compared with morbidly obese women. However, the bariatric surgery group was more likely to have venous thromboembolisms, to require a blood transfusion, to have their labor induced and to experience fetal growth restriction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 42 publications
0
35
1
2
Order By: Relevance
“…There was considerable variability across studies in the reported frequency of birth defects, likely due to differences in ascertainment and inclusion criteria. For example, Abenhaim et al used hospital discharge data, did not describe birth defect inclusion criteria, and reported less than one per cent of exposed and unexposed infants as having a birth defect . In contrast, Parent et al defined birth defects as any malformation diagnosis on the birth certificate or delivery discharge diagnoses (International Classification of Diseases codes 740‐756, excluding chromosomal abnormalities) and reported 22% and 16% of infants were affected in the exposed and unexposed groups, respectively .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was considerable variability across studies in the reported frequency of birth defects, likely due to differences in ascertainment and inclusion criteria. For example, Abenhaim et al used hospital discharge data, did not describe birth defect inclusion criteria, and reported less than one per cent of exposed and unexposed infants as having a birth defect . In contrast, Parent et al defined birth defects as any malformation diagnosis on the birth certificate or delivery discharge diagnoses (International Classification of Diseases codes 740‐756, excluding chromosomal abnormalities) and reported 22% and 16% of infants were affected in the exposed and unexposed groups, respectively .…”
Section: Resultsmentioning
confidence: 99%
“…Five studies evaluated the association between any bariatric surgery procedure and any birth defect . In these five studies, estimates of association ranged from 0.7 to 1.9, with four of the five studies reporting estimates greater than 1.0 (range: 1.1‐1.9) (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…En fant også hyppigere forekomst av blodtransfusjon etter fødsel og venøse tromboembolismer hos denne gruppen kvinner (9). Kjaer og medarbeidere finner imidlertid ikke belegg i sin studie for å si at risikoen for indusert fødsel er økt hos denne gruppen kvinner, sammenliknet med en kontrollgruppe (10).…”
Section: • • •unclassified
“…Enkelte studier har avdekket en høyere risiko for å få barn som er små for alderen (13), og også en høyere forekomst av intrauterin veksthemning (14). Abenhaim og medarbeidere viser i sin ferske studie til funn som peker i retning av at intrauterin veksthemning faktisk forekommer hyppigere hos kvinner som har gjennomgått fedmekirurgi, sammenliknet med sykelig overvektige kvinner (9). «Enkelte studier har avdekket en høyere risiko for å få barn som er små for alderen.» Den registerbaserte kohortstudien til Kjaer og medarbeidere konkluderer med at nyfødte av mødre som har gjennomgått fedmekirurgi, har lavere fødselsvekt, lavere gestasjonsalder og 2,3 ganger høyere risiko for å vaere SGA-barn sammenliknet med en matchende gruppe kvinner som ikke har gjennomgått fedmekirurgi.…”
Section: Lavere Fødselsvekt Preterm Fødselunclassified
“…Five studies were included in our review of IUGR rates in respect to bariatric surgery [14,16,[22][23][24] . Individually, they found either no difference or an increased rate of IUGR among the bariatric surgical patient as compared to their control.…”
Section: Iugrmentioning
confidence: 99%